2019
DOI: 10.1186/s13071-019-3510-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal tapeworms on the gut microbiota of the common carp, Cyprinus carpio

Abstract: Background Parasitic protozoans, helminths, alter the gut microbiota in mammals, yet little is known about the influence of intestinal cestodes on gut microbiota in fish. In the present study, the composition and diversity of the hindgut microbiota were determined in the intestine of common carp ( Cyprinus carpio ) infected with two tapeworm species, Khawia japonensis and Atractolytocestus tenuicollis . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…The gastrointestinal microbiota of diseased farmed yellowtail kingfish was dominated by an uncultured Mycoplasmataceae sp. Members of this family are typically found in the gut of farmed fish including Atlantic salmon, rainbow trout and common carp [48][49][50]. In our study, we found that this member was prevalent in diseased fish (both at the early and late stage of gut enteritis) when compared to healthy fish, indicating a potential harmful effect of these bacteria.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The gastrointestinal microbiota of diseased farmed yellowtail kingfish was dominated by an uncultured Mycoplasmataceae sp. Members of this family are typically found in the gut of farmed fish including Atlantic salmon, rainbow trout and common carp [48][49][50]. In our study, we found that this member was prevalent in diseased fish (both at the early and late stage of gut enteritis) when compared to healthy fish, indicating a potential harmful effect of these bacteria.…”
Section: Discussionsupporting
confidence: 50%
“…The gastrointestinal microbiota of diseased farmed yellowtail kingfish was dominated by an uncultured Mycoplasmataceae sp. Members of this family are typically found in the gut of farmed fish including Atlantic salmon, rainbow trout and common carp [48][49][50]. In our study, we found that this Each polygon represents an ontology term, with their size corresponding to the numbers of genes involved in the associated pathway.…”
Section: Discussionmentioning
confidence: 65%
“…As the dominant constituent here in poor performing fish, the occurrence of a single ASV related to an uncultured Mycoplasmataceae raises questions around its association with disease. As a member of this bacterial family, Mycoplasma have been previously identified in the gut of other fish such as Atlantic salmon, Chinook salmon (Oncorhynchus tshawytscha), zebrafish (Danio rerio), common carp (Cyprinus carpio), largemouth bronze gudgeon (Coreius guichenoti) and rainbow trout [38][39][40][41][42][43][44]. While recent genome reconstruction indicates a mutualistic lifestyle of this organism in the intestine of certain species like Atlantic salmon and hadal snailfish (Pseudoliparis swirei) [45,46], for others it has been associated with disease [42].…”
Section: Discussionmentioning
confidence: 99%
“…As the dominant constituent here in poor performing sh, the occurrence of a single ASV related to an uncultured Mycoplasmataceae raises questions around its association with disease. As a member of this bacterial family, Mycoplasma have been previously identi ed in the gut of other sh such as Atlantic salmon, Chinook salmon (Oncorhynchus tshawytscha), zebra sh (Danio rerio), common carp (Cyprinus carpio), largemouth bronze gudgeon (Coreius guichenoti) and rainbow trout [38][39][40][41][42][43][44]. While recent genome reconstruction indicates a mutualistic lifestyle of this organism in the intestine of certain species like Atlantic salmon and hadal snail sh (Pseudoliparis swirei) [45,46], for others it has been associated with disease [42].…”
Section: Discussionmentioning
confidence: 99%